Prevalence of thromboembolic events and status of prophylactic anticoagulant therapy in hospitalized patients with COVID-19 in Japan. Issue 6 (June 2021) - Fujiwara, Sho; Nakajima, Mikio; Kaszynski, Richard H.; Fukushima, Kazuaki; Tanaka, Masaru; Yajima, Keishiro; Kobayashi, Taiichiro; Sekiya, Noritaka; Yamamoto, Yasuhiro; Miwa, Maki; Ishihata, Ayaka; Yamauchi, Yuko; et al.
Abstract: Introduction: One of the most prominent and concerning complications associated with coronavirus disease 2019 (COVID-19) is venous and arterial thromboembolisms. The aim of the present study was to delineate the prevalence of thromboembolic events and the current status of prophylactic anticoagulation therapy in patients with COVID-19 in Japan. Methods: Between February 1 and August 31, 2020, we performed a dual-center, retrospective cohort study based on data obtained from the medical charts of COVID-19 patients admitted to healthcare facilities in Japan. The primary outcome was any thromboembolic event including pulmonary embolism (PE), deep vein thrombosis (DVT), myocardial infarction, ischemic stroke and other systemic thromboemboli. Results: During the study period, we extracted 628 consecutive patients admitted for COVID-19. Prophylactic anticoagulant therapy was administered in 63 (10%) patients of whom 20 (31.7%) were admitted to the intensive care unit (ICU). Thromboembolic events occurred in 18 (2.9%) patients (14.3% of patients in ICU and 2.2% of patients in the general wards). DVT were detected in 13 (2.1%) patients, PE in 11 (1.8%), and both DVT and PE in 6 (0.96%) patients. An increasing prevalence in thromboembolic events was noted with progressive clinical severity. Overall in-hospital mortality was 4.8%. Conclusions: Prophylactic anticoagulation therapy was administered in only 10% of all hospitalized COVID-19 patients. The prevalence of any thromboembolic events was 2.9% in COVID-19 patients with most events occurring in severe and critical patients. Therefore, prophylactic anticoagulation therapy may be warranted in severe and critical patients but in asymptomatic to moderate patients the practice remains controversial.